Periodized Core And Resistance-Based Strength Training Effects On Service Accuracy In Intermediate Tennis Players - Muhammad Dicky Saputra; Siti Baitul Mukarromah; Sugiarto (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
The objective of this study is to evaluate the impact of periodized core training and resistance-based strength training on enhancing service accuracy, as well as to compare the efficacy of these two training modalities among intermediate tennis players.  This study used an experimental method with a two-group pre-test and post-test design.  There were 16 intermediate tennis players from Club TitikTemuTennis in the sample. They were split into two groups: the periodized core training group and the resistance-based strength training group.  The training program took place over the course of one month, with three sessions per week for a total of 12 sessions.  The research tools used a test to see how well people could serve tennis balls.  Descriptive statistics, paired sample t-tests, and independent sample t-tests were used to look at the data.  The findings indicated that both training methods significantly enhanced service accuracy.  The periodized core training group gained an average of 10.50 points, while the resistance-based strength training group gained 7.75 points.  The comparison test showed that periodized core training was better than resistance-based strength training at helping people serve better.  So, systematic core stability training is a better way for intermediate tennis players to improve their serve accuracy.